CONVERGÊNCIA DAS RACIONALIDADES INSTRUMENTAL E SUBSTANTIVA NO AMBIENTE ORGANIZACIONAL: EVIDÊNCIAS NAS AÇÕES DE RESPONSABILIDADE SOCIAL EMPRESARIAL DA ASSOCIAÇÃO TABOARTE - Oliveira, Vanesca Ferreira de (2014)
This paper aims, through field research conducted in Entrepreneurial Community Association of Maracangalha Taboart, located in the Reconcavo Baiano, check, this productive organization, their organizational actions corroborate or refute the hypothesis proposed by this dissertation - "instrumental rationalities and substantive may be convergent in an organizational environment, with the product to Corporate Social Responsibility. "That is, if there TABOARTE in the presence of rationalities and, if so, whether they converge towards corporate social responsibility. Initially, it provided a theoretical framework on the topic, which addresses the issues of Organizational Studies, instrumental and Substantive Rationality and Social Responsibility - CSR. Utilizing the bibliographical, documentary research and Case Study Taboarte Association which is a non-profit society, with economic and social order. The objective of this work is to demonstrate the hypothesis whose operation will be demonstrated through specific objectives that have been conducted exploratory and through the collection of studies of academic materials, in order to: a) demonstrate evidence of the coexistence of rationalities; b) conceptualize instrumental and substantive rationality and demonstrates its convergence; c) conceptualize social responsibility in organizations; d) characterize the Taboarte Association. Exposing the diagnosis of history and reality of Taboarte, we analyze the dynamics of your everyday life, through their organizational processes, their actions and constituent elements of rationality. It is noteworthy that data from case study were extracted from bibliographic, documentary research, in addition to field research. All this context provides a critical analysis of the convergence of rationalities, in an organizational environment, with the product to Corporate Social Responsibility.